Anti-windup compensator design for LTI plants utilising negative imaginary and absolute stability theory. Issue 1 (2022) - Ghosh, Triparna; Bhowmick, Parijat
Abstract: This paper aims to present an Anti-Windup Compensator (AWC) design technique relying on the well-established Weston-Postlethwaite's linear conditioning scheme utilising the Negative Imaginary (NI) and absolute stability theories. The anti-windup technique ensures closed-loop stability of the overall scheme incorporating the effect of actuator saturation exploiting the absolute stability theory. It improves the performance during the period of actuator saturation by minimising the DC-gain of the disturbance signal. The NI and absolute stability-based approach offer an LMI-based technique to synthesize an anti-windup compensator that does not depend on the nominal controller. The feasibility and usefulness of the scheme are illustrated through a multi-variable system case study.